Linguistic foundations of research on specialized intercultural communication - Grucza, Sambor (Specialized Languages in Intercultural Communication, 2020)
The paper presents the linguistic foundations of research on intercultural specialized communication from the point of view of anthropocentric communicology. It must be assumed that in these studies, firstly, specialized intercultural communication is based on communication competence, within which one can distinguish (a) specialized language competence, (b) specialized discursive competence, (c) specialized cultural competence and (d) specialized intercultural competence. Secondly, it is necessary to distinguish between (i) specialized idiolects, specialized knowledges and specialized idiocultures, (ii) specialized polylects, specialized knowledges, and specialized polycultures, (iii) models of specialized languages, models of specialized knowledges, and models of specialized cultures. The paper discusses and develops these issues.